Nobiletin suppresses monocyte chemoattractant protein-1 (MCP-1) expression by regulating MAPK signaling in 3T3-L1 cells. (December 2016) - Yasunaga, Sho; Domen, Miku; Nishi, Kosuke; Kadota, Ayumu; Sugahara, Takuya
Highlights: Nobiletin suppresses both gene expression and secretion of MCP-1 in 3T3-L1 adipocytes. Nobiletin downregulates ERK phosphorylation independent of differentiation stages. Nobiletin reduces MCP-1 secretion and ERK phosphorylation in TNF-α-treated adipocytes. Nobiletin may contribute to improving chronic inflammation in obese adipose tissues. Abstract: Nobiletin is a major citrus flavonoid possessing several biological activities. Nobiletin has been reported to display anti-inflammatory activity and to reduce monocyte chemoattractant protein (MCP)-1 secretion by 3T3-L1 adipocytes. However, its mode of action remains unclear. In the present study, we investigated the suppressive effect of nobiletin on MCP-1 expression in 3T3-L1 cells and its underlying molecular mechanism. Nobiletin notably down-regulated the MCP-1 mRNA level during adipocyte differentiation. Nobiletin also reduced MCP-1 secretion by preadipocytes (undifferentiated cells), differentiated adipocytes, and hypertrophied adipocytes. Immunoblot analysis showed that nobiletin inhibits the phosphorylation level of extracellular signal-regulated kinase (ERK) in both preadipocytes and differentiated adipocytes. Moreover, nobiletin suppressed MCP-1 secretion by adipocytes induced by tumor necrosis factor (TNF)-α.